Plants of with conservation interest in at the Complutense University’s Biological Field Station - Castoldi, Elena; Benavent, Alberto; Molina, José Antonio (Lazaroa, 2014)
Nine species with conservation interest are recorded at the Complutense University’s Biological Field Station. These are the following: a) with regional interest: Ilex aquifolium L., Lilium martagon L., Sorbus latifolia (Lam.) Pers., and Taxus baccata L. (sensitive to habitat alteration); Juncus bulbosus L., Prunus padus L. subsp. padus, and Ranunculus valdesii Grau (vulnerable); Malus sylvestris (L.) Mill. (species of special interest); b) with European interest: Anacamptis morio (L.) R.M. Bateman, Pridgeon & M.W.Chase (near threatened).